Pelatihan Penerapan Potongan Harga Pada Layanan Dompet Digital OVO - Mumuh Mulyana; Abdul Roup; Sulastri Sulastri (Jurnal Abdimas Dedikasi Kesatuan, 2021)
The research method used is a case study, which takes one particular object for in-depth analysis by focusing on one problem. The data used are primary data and secondary data. Primary data were collected through questionnaires and direct observation with the customers of PT. International Visionet (OVO), while secondary data were obtained from books and other sources. Based on the results of the study, it shows that the digital wallet service of PT. Visionet Internasional is in the good category, this can be seen from the large number and increasing number of digital wallet service (OVO) users, and with various promos that customers can enjoy at various merchants, it keeps its users loyal to using digital wallet (OVO) services. With the discount, it has an impact on the customer's desire to re-establish cooperation and even recommends others to participate in using the digital wallet service application (OVO). Keywords: Service, OVO Digital Wallet